1997
DOI: 10.1002/chem.19970031213
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric [(Me3Sn)3Rh(SCN)6]: A Novel “Super‐Prussian‐Blue” Derivative Containing the Nonlinear ‐SCN‐Sn‐NCS‐ Spacer

Abstract: Abstract:The new coordination polymer [(Me,Sn'v)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…48 Not only transition metals, but also main group metals with chelate ligands, such as the (SnMe 3 ) + cation, are prospective linkers for binding the cyanometallate complexes and can be used in the synthesis of so called super Prussian blue structures based on the cyanometallates [M(CN) 6 ] nÀ . 68,69 We studied the interaction of the anionic cluster complexes [Re 6 Se 8 (CN) 6 ] 4À and SnMe 3 Cl, varying the acidity of the medium, 53 and showed that the type of polymer formed is mainly determined by the synthesis conditions, i.e., the ''charge'' stoichiometry, the temperature, and pH of the medium. 70 Unlike with transition metals, the Sn atom has, as a rule, coordination number 5 (triangular bipyramid), with the methyl groups in the equatorial plane and the axial trans-positions available to the other ligands L for coordination.…”
Section: And Their Variation Depending On Metal Cation Complexesmentioning
confidence: 99%
“…48 Not only transition metals, but also main group metals with chelate ligands, such as the (SnMe 3 ) + cation, are prospective linkers for binding the cyanometallate complexes and can be used in the synthesis of so called super Prussian blue structures based on the cyanometallates [M(CN) 6 ] nÀ . 68,69 We studied the interaction of the anionic cluster complexes [Re 6 Se 8 (CN) 6 ] 4À and SnMe 3 Cl, varying the acidity of the medium, 53 and showed that the type of polymer formed is mainly determined by the synthesis conditions, i.e., the ''charge'' stoichiometry, the temperature, and pH of the medium. 70 Unlike with transition metals, the Sn atom has, as a rule, coordination number 5 (triangular bipyramid), with the methyl groups in the equatorial plane and the axial trans-positions available to the other ligands L for coordination.…”
Section: And Their Variation Depending On Metal Cation Complexesmentioning
confidence: 99%
“…These MOFs with microporosity might be good candidates for storage of small molecules like hydrogen, and further investigation will be performed. As far as we known, the numerous MOFs of α-Po topology are 2-fold or 3-fold interpenetrated frameworks. , Complexes 1 − 3 are the scarce examples of non-interpenetrated structures of the topology. The topologies of these complexes are similar to Zn 2 (trz) 2 (ox) which are constructed from comparable (4,4) layers that are further connected to 3-D networks by bridging ligands …”
Section: Resultsmentioning
confidence: 99%
“…The stock solution of K 3 [Rh III (SCN) 6 ] was prepared according to the literature procedure with some modifications. 31 An aqueous solution of potassium thiocyanate (1.0 M, 30 mL) was heated to 100 °C and magnetically stirred, followed by the slow addition of an aqueous solution of rhodium(III) chloride trihydrate (0.57 M, 10 mL) for 2 h. After the reaction solution was cooled to room temperature, distilled water (25 mL) was slowly added to the obtained slurry and then evaporated under reduced pressure. After this procedure was repeated two times, absolute ethanol was added to the residue to extract the crude products.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%